A numerical study on the optimization of a granular medium to infer the axial stress in slender structures. Issue 10 (2nd October 2016) - Bagheri, Abdollah; Rizzo, Piervincenzo; Al-Nazer, Leith
ABSTRACT: The in-situ measurement of axial stress in beams may prevent structural anomalies, such as unexpected buckling. We describe the coupling mechanism between highly nonlinear solitary waves (HNSWs) propagating along a granular system and a beam in contact with the granular medium to assess the ability of HNSWs to measure axial stress. One and two straight chains of particles were considered and the effect of the particles' diameter and material was evaluated to find those designs that maximize the sensitivity to the variation of axial stress. In the future, our findings may be used to develop a novel system for the nondestructive inspection of beams.